OP0126 A Genome-Wide Association Study Identifies a New Locus Asociated with the Response to Anti-TNF Therapy in Rheumatoid Arthritis. (9th June 2015) - Tornero, J.; Fernández-Nebro, A.; Blanco, F.; Ortiz, A.; Cañete, J.D.; Maymό, J.; Alperi-Lόpez, M.; Fernández-Gutierrez, B.; Olivé, A.; Corominas, H.; Erra, A.; Acosta Colman, M.I.; et al.
Abstract : Background: Anti-Tumor Necrosis Factor (Anti-TNF) drugs are biologic agents commonly used to treat rheumatoid arthritis (RA). However, there is considerable heterogeneity in the response to this therapy and approximately 25% of anti-TNF-treated patients do not show a significant clinical improvement. The high costs of this therapy and the possibility of alternative biologic treatments of similar efficacy are raising the need for biomarkers of response to anti-TNF therapy. Objectives: We conducted a Genome-Wide Association Study (GWAS) to identify the genetic variation associated with the response to anti-TNF therapy in RA. Methods: A total of 372 RA patients treated with an anti-TNF agent (adalimumab, etanercept or infliximab) as their first biologic therapy were recruited in the discovery phase. All patients were diagnosed as RA according to the ACR classification criteria, had >2 years of follow-up since diagnosis and were naïve to any biologic therapy. All cases were Caucasian European and with all four grandparents born in Spain. An independent cohort of 245 RA patients treated with an anti-TNF therapy and also collected by the IMIDC was used to validate the most significant genetic associations from the GWAS. The patient recruitment criteria were the same as for the discovery phase. Results: A total of 3 SNPs were found to meet the significance threshold in the GWASs. From these, the MED15 association with etanercept reached a genome-wide level of statistical significance ( P =1.24e-8). The other two highly significant associated loci were ARMC2 ( P =6.22e-8) MAFB P =6.26e-8), and were found in the global and etanercept-infliximab GWASs, respectively. Using the independent patient cohort we validated the association at MED15 with the response to etanercept ( P <0.05, same direction of effect) and found a suggestive evidence for MAFB ( P =0.056, same direction of effect). Conclusions: In the present GWAS we have identified a new genetic region associated with the response to anti-TNF therapy and we have found additional evidence for a previously associated locus. The results of this study are an important contribution to the pharmacogenetics of this prevalent disease. Disclosure of Interest: None declared